Endothelialized microvessels fabricated by microfluidics facilitate osteogenic differentiation and promote bone repair. (1st April 2022) - Wang, Jiayuan; Wang, Huan; Wang, Yong; Liu, Zhao; Li, Zexi; Li, Jiaying; Chen, Qixin; Meng, Qingchen; Shu, Wenmiao Will; Wu, Junxi; Xiao, Can; Han, Fengxuan; et al.
Abstract: In bone tissue engineering, vascularization is one of the critical factors that limit the effect of biomaterials for bone repair. While various approaches have been tried to build vascular networks in bone grafts, lack of endothelialization still constitutes a major technical hurdle. In this study, we have developed a facile technique to fabricate endothelialized biomimetic microvessels (BMVs) from alginate-collagen composite hydrogels within a single step using microfluidic technology. BMVs with different sizes could be readily prepared by adjusting the flow rate of microfluids. All BMVs supported perfusion and outward penetration of substances in the tube. Endothelial cells could adhere and proliferate on the inner wall of tubes. It was also found that the expression of CD31 and secretion of BMP-2 and PDGF-BB were higher in the rat umbilical vein endothelial cells (RUVECs) in BMVs than those cultured on hydrogel. When co-cultured with bone marrow mesenchymal stem cells (BMSCs), endothelialized BMVs promoted the osteogenic differentiation of BMSCs compared to those in acellular BMV group. In vivo, markedly enhanced new bone formation was achieved by endothelialized BMVs in a rat critical-sized calvarial defect model compared to those with non-endothelialized BMVs or without BMVs. Together, findings from both in vitro and in vivo studies have proven that endothelialized BMVs function to facilitate osteogenesis and promote bone regeneration, and therefore might present an effective strategy in bone tissue engineering. Statement of significance: In bone tissue engineering, limited vascularization is one of the critical factors that limit the effect of biomaterials for bone repair. In this study, we developed a facile technique to fabricate endothelialized biomimetic microvessels (BMVs) from alginate-collagen composite hydrogels within a single step using microfluidic technology. Both in vitro and in vivo studies have proven that endothelialized BMVs function to facilitate osteogenesis and promote bone regeneration, and therefore might present an effective strategy in bone tissue engineering. Graphical abstract: Image, graphical abstract